Akselerasi Pengembangan Kawasan Geotourism melalui Pendampingan Pemetaan Digital berbasis Potensi Wilayah di Desa Pusung Kapal - Urfan, Faiz; Sari, Rima Meilita; Ridhwan; Rella, Sindiy Amay; Zakir, Muhammad (Jurnal Pemberdayaan Masyarakat, 2025)
Pusung Kapal Village has ecological and geological potential, positioning it as a promising geotourism destination. However, its current utilization remains limited due to insufficient geospatial information regarding the area's potential and a lack of facilitated spatial data-driven tourism management. This community sevice program was conducted in Pusung Kapal Village, Seruway District, Aceh Tamiang Regency, Aceh Province. The primary objective of this project was to accelerate geotourism development through territorial potential mapping and the implementation of geospatial technology-based innovations. The target of community service is the community and tourism-aware groups in Pusung Kapal Village. This service aims to accelerate the development of geotourism through mapping the potential of the area and implementing innovations based on geospatial technology. The activities consist of a preparation stage, an implementation stage, an evaluation stage, and a reporting stage. The outcomes derived from this endeavor include 1) enhanced community competency in geotourism mapping and promotion, 2) the distribution map of geotourism site footprints; 3) the geotourism promotional video of Pusung Kapal Village, 4) the geotourism information website of Pusung Kapal Village. This activity is expected to foster community self-reliance in their efforts to advance geotourism destinations within Pusung Kapal Village.